Sertão e sertanejos em Gustavo Barroso: o controle de espaços e sujeitos - Zaniboni, Isabela de Lorena (2023)
That dissertation paper seeks to identify how the intelectual cearense Gustavo Barroso (1888-1959) throught of a analysis of your books from 1912-1930 make a sertões, sertanejo, cangaceiro e himself history. Throught ideas of writers Michel de Certeau with your thought of Operação Historiográfica and Michel Foucault about you tought about subject, I want with this work to understand how Gustavo Barroso do the subject in you write, of himself and the another and who is not considered subject. The books chosen for the work is: Terra de Sol (1912), Praias e Várzeas (1915), Heróes e Bandidos (1917), Alma Sertaneja (1923) e Almas de Lama e de Aço (1930). Books whit space ant time differents. That show Gustavo Barroso development tought about the subject and yours space, men stabilitys, resistants Against the outer. Different features conform speaks the character, giving consciense for the specifics people. From this reflexion, I looking to understand too how Barroso helps to create pictures in your write of the area whos speaks, doing that generalized and naturalized speeches keeping for the anothers.